Desentralisasi Dan Kekhususan Pelaksanaan Otonomi Daerah Otorita Ibu Kota Nusantara - M. Rizki Nurdin (Universitas Islam Indonesia, 2022)
This study discusses decentralization and the specificity of implementing regional autonomy as the authority for the capital city of Nusantara. The purpose of this research is to identify the decentralization and the specificity of implementing regional autonomy as the authority for the capital city of Nusantara. This research uses normative juridical methods. The materials used are primary and secondary legal materials obtained from literature studies and qualitative analysis. Based on the results of the research, this study concludes that: Law Number 3 of 2022 is the legal basis for the establishment of a regional government specifically for the capital city of Nusantara. The legal basis regulates the peculiarities of Nusantara, namely the authorities, rights, obligations, duties and responsibilities in administering government in the national capital. The capital city of the Nusantara is a regional government, therefore the administration of government continues to apply regional autonomy and co-administration with the principle of broadest autonomy. However, there are several concepts of decentralization and regional autonomy that are inconsistent with practice in the archipelago capital city authority areas, namely the Institutional Authority Board of the Capital City of Nusantara, the appointment of the Head of the Nusantara Capital Authority by the President and the abolition of the Regional House of Representative institution in the Nusantara Capital City.Key Words: Decentralization; specificity; indonesian capital authority AbstrakPenelitian ini membahas mengenai desentralisasi dan kekhususan pelaksanaan otonomi daerah otorita ibukota Nusantara. Tujuan penelitian ini untuk mengetahui desentralisasi dan kekhususan pelaksanaan otonomi daerah otorita ibu kota Nusantara. Penelitian ini menggunakan metode penelitian hukum yuridis normatif. Bahan yang dipakai ialah bahan hukum primer maupun sekunder yang didapatkan dari studi kepustakaan dan analisis secara kualitatif. Berdasarkan dari hasil penelitian, maka penelitian ini menyimpulkan: Undang-Undang Nomor 3 Tahun 2022 merupakan dasar hukum pembentukan pemerintahan daerah khusus ibu kota Nusantara. Dasar hukum tersebut mengatur kekhususan Nusantara yaitu kewenangan, hak, kewajiban, tugas, dan tanggung jawab dalam menyelenggarakan pemerintahan di ibu kota negara. Ibu Kota Nusantara merupakan pemerintahan daerah maka dari itu penyelenggaraan pemerintahan tetap menerapkan otonomi daerah dan tugas pembantuan dengan prinsip otonomi seluas-luasnya. Namun terdapat beberapa konsep desentralisasi dan otonomi daerah yang tidak sesuai dengan praktik di daerah otorita ibu kota Nusantara yaitu Kelembagaan Badan Otorita Ibu Kota Nusantara, pengangkatan Kepala Ototrita Ibu Kota Nusantara oleh Presiden dan pengapusan lembaga Dewan Perwakilan Rakyat Daerah di Ibu Kota Nusantara.Kata-kata Kunci: Desentralisasi; kekhususan; otorita ibu kota nusantara